The molecular basis of flavonoid biosynthesis response to water, light, and temperature in grape berries - Shi, Tianci; Su, Yue; Lan, Yibin; Duan, Changqing; Yu, Keji (Frontiers in Plant Science, 2024)
Flavonoids, including proanthocyanidins (PAs), anthocyanins and flavonols are essential secondary metabolites that contribute to the nutritional value and sensory quality of grape berry and red wine. Advances in molecular biology technology have led to substantial progress in understanding the regulation of flavonoid biosynthesis. The influence of terroir on grape berries and wine has garnered increasing attention, yet its comprehensive regulatory network remains underexplored. In terms of application, environmental factors such as water, light, and temperature are more easily regulated in grapevines compared to soil conditions. Therefore, we summarize their effects on flavonoid content and composition, constructing a network that links environmental factors, hormones, and metabolites to provide a deeper understanding of the underlying mechanisms. This review enriches the knowledge of the regulatory network mechanisms governing flavonoid responses to environmental factors in grapes.